Ring‐Opening Metathesis Polymerization in Aqueous Media Using a Macroinitiator Approach. (6th July 2018) - Foster, Jeffrey C.; Varlas, Spyridon; Blackman, Lewis D.; Arkinstall, Lucy A.; O'Reilly, Rachel K.
Abstract: Water‐soluble and amphiphilic polymers are of great interest to industry and academia, as they can be used in applications such as biomaterials and drug delivery. Whilst ring‐opening metathesis polymerization (ROMP) is a fast and functional group tolerant methodology for the synthesis of a wide range of polymers, its full potential for the synthesis of water‐soluble polymers has yet to be realized. To address this, we report a general strategy for the synthesis of block copolymers in aqueous milieu using a commercially available ROMP catalyst and a macroinitiator approach. This allows for excellent control in the preparation of block copolymers in water. If the second monomer is chosen such that it forms a water‐insoluble polymer, polymerization‐induced self‐assembly (PISA) occurs and a variety of self‐assembled nano‐object morphologies can be accessed.